PATH39 Malformation risks of antiepileptic drugs in pregnancy: an update from the UK Epilepsy and Pregnancy Register. Issue 11 (22nd October 2010) - Kennedy, F; Morrow, J; Hunt, S; Russell, A; Smithson, W H; Parsons, L; Robertson, I; Irwin, B; Delanty, N; Morrison, P J; Craig, J
Abstract : Aim: To assess the relative risk of major congenital malformations (MCM) from exposure to anti-epileptic drugs (AEDs) during pregnancy. Methods: 15 year prospective observational study from 1996 until 2009. The outcome measure is the MCM rate. Results: Informative outcomes were available for 5802 cases. The risk of MCM was significantly higher in women on AEDs during pregnancy (n=5376) in comparison to those on no treatment (n=426), RR: 1.55 (95% CI 1.13 to 2.14), and significantly higher in polytherapy (n=1183) than monotherapy (n=4193), RR: 1.60 (95% CI 1.19 to 2.15). The risk to those on valproate monotherapy was more than double that for those on either carbamazepine (RR 2.35, 95% CI 1.55 to 3.57) or lamotrigene (RR 2.40, 95% CI 1.57 to 3.68). 245 and 362 informative outcomes were obtained for topiramate and levetiracetam respectively, with MCM rates of 7.1% (95% CI 4.5 to 11.0%) and 2.5% (95% CI 1.3 to 4.7%). There were 3/83 cases of MCM in Topiramate monotherapy and 14/162 cases in polytherapy. There were no cases of MCMs in levetiracetam monotherapy and 9/229 cases levetiracetam polytherapy. Conclusions: AED exposure during pregnancy increases the risk of MCM in the babies of women with epilepsy. Polytherapy exposure has a higher risk than monotherapy. Valproate exposure carries higher MCM risk than any other AED. Lowest risk is associated with carbamazepine or lamotrigene monotherapy. Results for levetiracetam, although numbers are small, look promising.